Revisiting: The Relationship between Hadith and Entrepreneurship-Based Islamic Education in Islamic Educational Institutions - Suhairi; Ahmad Mohammad Tidjani (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
This research is motivated by the low learning outcomes of students who are below the KKM standard in the subject of Islamic Cultural History (SKI). This study aims to (1) determine the application of the concept map learning method at MA Plus Miftahul Khoer (2) Student learning outcomes in the subject of Islamic Cultural History at MA Plus Miftahul Khoer and (3) The Effect of the Application of the Concept Map Learning Method on Student Learning Outcomes in the Subject of Islamic Cultural History at MA Plus Miftahul Khoer. This research is a quantitative survey research that is associative in nature. The population is 50 students, and the sample is also 50 students. Data collection techniques are through questionnaires, interviews, observations and documentation. The results of the study show that: (1) The application of the concept map learning method at MA Plus Miftahul Khoer is all classified as good. This means that the majority of students agree that SKI learning using the concept map method has an effect on learning outcomes. (2) Student learning outcomes in the subject of Islamic Cultural History at MA Plus Miftahul Khoer have increased significantly after applying the concept map learning method which previously used the conventional method, namely lectures. This can be seen from the average learning outcomes of students with the lecture learning method, namely obtaining a score of 50.4 and the average learning outcomes of students after applying the concept map learning method, namely obtaining a score of 88.8. (3) The Effect of Applying the Concept Map Learning Method on Student Learning Outcomes in the Subject of Islamic Cultural History at MA Plus Miftahul Khoer 51% and 49% influenced by other factors that were not examined.